PERLINDUNGAN HUKUM TERHADAP MEREK (TINJAUAN TERHADAP MEREK DAGANG TUPPERWARE VERSUS TULIPWARE) - Sulastri, Sulastri; Satino, Satino; W, Yuliana Yuli (Jurnal Yuridis, 2018)
According to Article 1 Act No.15 of 2001 on Marks, the meaning of Marks is a sign in the form of pictures, names, words, letters of numbers, color arrangements, or combinations of those elements which have differentiating power and are used in the world of trade in goods or services. In the world of trades often occur brand violations. Branding violations are essentially committed by parties that have no good ethics to gain a profit, which can harm a legitimate brand owner. The purpose of this study is to know the legal protection against brand disputes. The method used in this research is the normative juridical approach method because this legal research uses data from library materials (secondary data). The results of this study illustrate that legal protection for a person or owner of a brand in the event of a brand dispute.